Predicting Hedge Fund Performance with Style - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2009)
I apply the endogenous benchmark approach to the study of hedge funds. I find that including an investment style benchmark significantly reduces within style correlations in hedge fund residuals. Also, the performance spread between high past alpha t-statistic (a risk-adjusted information ratio) funds and low past alpha t-statistic funds increases dramatically when performance is measured relative to fund investment style. There appears to be valuable information in investment style performance that can aid in fund selection.